2016
DOI: 10.1242/jcs.181008
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense-mediated mRNA decay in humans at a glance

Abstract: Nonsense-mediated mRNA decay (NMD) is an mRNA quality-control mechanism that typifies all eukaryotes examined to date. NMD surveys newly synthesized mRNAs and degrades those that harbor a premature termination codon (PTC), thereby preventing the production of truncated proteins that could result in disease in humans. This is evident from dominantly inherited diseases that are due to PTC-containing mRNAs that escape NMD. Although many cellular NMD targets derive from mistakes made during, for example, pre-mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
290
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(313 citation statements)
references
References 133 publications
7
290
1
2
Order By: Relevance
“…Furthermore, SMG6 is the endonuclease during NMD, which cleaves the NMD targets and initiates exonucleolytic decay of the RNA degradation intermediates from both the 5′ and 3′ ends (Schmidt et al , 2015; Hug et al , 2016; Kurosaki & Maquat, 2016). We then performed SMG6 knock‐down (Appendix Fig S14A) and showed that similar to UPF1, repression of SMG6 significantly reduced the ISG up‐regulation in response to HNRNPC knock‐down (Appendix Fig S14B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, SMG6 is the endonuclease during NMD, which cleaves the NMD targets and initiates exonucleolytic decay of the RNA degradation intermediates from both the 5′ and 3′ ends (Schmidt et al , 2015; Hug et al , 2016; Kurosaki & Maquat, 2016). We then performed SMG6 knock‐down (Appendix Fig S14A) and showed that similar to UPF1, repression of SMG6 significantly reduced the ISG up‐regulation in response to HNRNPC knock‐down (Appendix Fig S14B).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, our data showed that the two critical factors for initiation of the NMD pathway, UPF1 and SMG6, are required for the interferon response upon HNRNPC repression. SMG6 has endonuclease activity, which results in direct cleavage of the NMD targets and initiation of the exonucleolytic RNA decay from both the 5′ and 3′ ends (Eberle et al , 2009; Schmidt et al , 2015; Hug et al , 2016; Kurosaki & Maquat, 2016). Therefore, we propose that the Alu dsRNA sequences are end products of a series of RNA decay processes, rather than just direct products of SMG6.…”
Section: Discussionmentioning
confidence: 99%
“…This similarity between mouse phenotypes suggested that, like mutations in TEK, loss-of-function mutations in ANGPT1 may con- result in a truncated product containing the N-terminal oligomerization domain, but lacking the full C-terminal receptor binding domain that is essential for interaction with the TEK receptor. Conversely, the p.R494* variant introduces a stop codon just 5 residues prior to the normal termination codon in exon 9, and will likely escape NMD as premature truncations located in the final exon do not induce this mRNA cleanup system (17). The resulting protein product would contain the complete oligomerization domain, but lack the terminal 5 amino acids of the receptor binding domain.…”
Section: Loss-of-function Mutations In Angpt1 Are Associated With Hummentioning
confidence: 99%
“…Cooperation among RNA helicases, RNA-binding proteins, and microRNAs triggers mRNA degradation by recognizing specific structural or sequence features of target mRNAs (Balagopal et al 2012;Wu and Brewer 2012). One of the best characterized RNA surveillance machineries is nonsense-mediated mRNA decay (NMD), which eliminates premature termination codon (PTC)-containing aberrant mRNAs that produce potentially harmful truncated proteins (Schweingruber et al 2013; Lykke-Andersen and Jensen 2015; Kurosaki and Maquat 2016). In human cells, spliced mRNAs harbor exon junction complexes (EJCs), comprising EIF4A3, Y14 (RBM8A), MAGOH, and CASC3, positioned at 20-24 nt upstream of the exon-exon boundary, as a consequence of pre-mRNA splicing.…”
mentioning
confidence: 99%